Application of geoinformation systems in the armed forces and other military formations in the Republic of Kazakhstan - Zakiev, Erlan; Pankov, Sergey; Kalabay, Komesh (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The purpose of the paper is to present the importance of geoinformation systems (GIS) in the process of geotopographic support to all levels of command as well as the necessity of developing the GIS platform concept based on geoinformation data as a support to decision making. Methods: Besides an analytical approach to some of foreign experiences in developing GIS and a sample analysis, the authors give the content and the architecture of the adopted program named „Development of a special GIS platform for the defense and security of the Republic of Kazakhstan“. Results: The paper presents the structures and the level achieved in the development of the single geographic information platform (SGIP) which aims at helping the state to create modern army and efficiently use geoinformation technologies in the support to the armed forces of Kazakhstan. Conclusion: The importance of creating, at the state level, a unique geographic information space based on the integration of geospatial data at all levels of command has been pointed out as well as the importance of eliminating overspending while creating geoinformation data. In addition, efficient usage of geoinformation technologies will contribute to better combat control of troops and armament thus creating a modern and ready military.